Теоретико-методологічні основи формування та функціонування системи принципів цивільного судочинства : автореф. дис. - Кройтор, В. А.; Kroitor, V. A.; ORCID: http://orcid.org/0000-0002-1849-5721 (Харків : Харківський національний університет внутрішніх справ, 2021)
У дисертації сформульовано та обґрунтовано концептуальну модель трансформації системи принципів цивільного судочинства з урахуванням концептів чинного цивільного процесуального законодавства, ст. 6 Конвенції про захист прав людини та основоположних свобод та рішень Європейського суду з прав людини. Розгляд структури та системи принципів цивільного судочинства дозволяє зробити висновок, що вони перебувають у тісному взаємозв’язку та взаємозумовленості, тобто вибудовується певна модель системи цих принципів. За своїми сутнісними ознаками модель трансформації системи принципів цивільного судочинства визначається: розумінням сутності принципів цивільного судочинства з позицій інтегративного (природно-позитивістського) праворозуміння; співвідношенням та реалізацією загальновизнаних принципів і норм міжнародного права та принципів, закріплених у національному законодавстві; функціональним призначенням принципів цивільного судочинства, яке виявляється в правотворчій та в правозастосовчій діяльності; підвищення ефективності правового регулювання за допомогою потенціалу принципів цивільного судочинства шляхом наділення їх якістю самостійного нормативного регулятивного засобу. Аргументовано положення, що теоретико-прикладна модель механізму реалізації принципів цивільного судочинства охоплює три структурні рівні: законодавче закріплення принципів цивільного судочинства, реалізацію принципів цивільного судочинства нормотворчої діяльності законодавця, реалізацію принципів цивільного судочинства у правозастосовній діяльності. Виокремлення цих рівнів дозволить більш чітко окреслити коло проблем (і шляхи їх вирішення), пов’язаних із реалізацією принципів цивільного судочинства як ефективного регулятора суспільних відносин.

The author of the dissertation has formulated and substantiated the conceptual model of transformation of the system of principles of civil justice taking into account the concepts of the current civil procedural legislation, the Art. 6 of the Convention for the Protection of Human Rights and Fundamental Freedoms and decisions of the European Court of Human Rights. Review of the structure and system of principles of civil justice allows us to conclude that they are closely interrelated and interdependent, that is, a certain model of the system of these principles is built. The model of transformation of the system of principles of civil justice according to its essential features is determined by: understanding the essence of the principles of civil justice from the standpoint of integrative (natural and positive) legal understanding; the correlation and implementation of generally accepted principles and norms of international law and the principles enshrined in national legislation; functional purpose of the principles of civil justice, which is manifested in lawmaking and law-enforcement activities; improving the effectiveness of legal regulation through the potential of the principles of civil justice by giving them the quality of an independent regulatory mean. It has been argued that theoretical and applied model of the mechanism for implementing the principles of civil justice covers three structural levels: legislative consolidation of the principles of civil justice, implementation of the principles of civil justice of law-making activity of the legislator, implementation of the principles of civil justice in law-enforcement activity. The allocation of these levels will allow us to define more clearly the range of problems (and ways to solve them) related to the implementation of the principles of civil justice as an effective regulator of public relations. Based on the allocated essential features of the principles of civil justice and the existing doctrinal approaches to their understanding, the author has offered to define the concept of principles of civil justice, which should be recognized as the original, fundamental principles that are objective in nature and subjective in form of expression, the express the most general nature of legal requirements relating to the court and participants in civil proceedings, they are universal, since they affect all civil procedural norms, need to be taken into account in each case of legal enforcement, are imperative, because deviations from them are unacceptable and determine the process of formation, operation and development of the entire field of civil procedural law. The division of the principles of civil justice into two subsystems: the fundamental principles of civil justice and principles of civil justice of Ukraine, which underline the specific features of justice in civil cases, allows us to emphasize the practical component of this classification. The principles that can be included in the group of fundamental principles of civil proceedings can be characterized as absolute, i.e. those that do not allow restrictions. Accordingly, the violation of which must be an unconditional ground for revocation of the court decision. Regarding the group of principles of civil justice of Ukraine, which emphasize the specific features of justice in civil cases, we believe that they are not absolute, i.e. may be limited. Accordingly, the violation of which may entail the revocation of the court decision. It has been concluded that one of the most important issues for the functioning of the system of principles of civil procedural law is the relationship nature between them. The elements in the system are connected to each other, they are not on their own terms. There is a clear relationship and interdependence of the principles that are part of the system during the study of the system of principles of civil justice. The principles of civil justice do not exist outside the system, but are closely interconnected and supplemented by one another, their existence is determined by the current level of society’s development, the state of the judiciary and judicial system in the country, resulting in a special scientific and theoretical formation – the system of principles of civil justice. The system of principles of civil justice is a holistic system and meets its requirements; the elements of the system of principles are not combined mechanically, but are included into the system and acquire qualities that were not inherent separately in them.

В диссертации сформулирована и обоснована концептуальная модель трансформации системы принципов гражданского судопроизводства с учетом концептов действующего гражданского процессуального законодательства, ст. 6 Конвенции о защите прав человека и основных свобод и решений Европейского суда по правам человека. Рассмотрение структуры и системы принципов гражданского судопроизводства позволяет сделать вывод, что они находятся в тесной взаимосвязи и взаимообусловленности, то есть выстраивается определенная модель системы этих принципов. По своим сущностным признакам модель трансформации системы принципов гражданского судопроизводства определяется: пониманием сущности принципов гражданского судопроизводства с позиций интегративного (естественнопозитивистского) правопонимания; соотношением и реализацией общепризнанных принципов и норм международного права и принципов, закрепленных в национальном законодательстве; функциональным назначением принципов гражданского судопроизводства, которое проявляется в правотворческой и в правоприменительной деятельности; повышением эффективности правового регулирования с помощью потенциала принципов гражданского судопроизводства путем наделения их качеством самостоятельного нормативного регулятивного средства. Аргументировано положение, что теоретико-прикладная модель механизма реализации принципов гражданского судопроизводства охватывает три структурных уровня: законодательное закрепление принципов гражданского судопроизводства, реализацию принципов гражданского судопроизводства в нормотворческой деятельности законодателя, реализацию принципов гражданского судопроизводства в правоприменительной деятельности. Выделение этих уровней позволит более четко очертить круг проблем (и пути их решения), связанных с реализацией принципов гражданского судопроизводства как эффективного регулятора общественных отношений.
Автореферат дисертації на здобуття наукового ступеня доктора юридичних наук
Theoretical and Methodological Foundations for the Formation and Functioning of the System of Principles of Civil Justice System
Кройтор, В. А. Теоретико-методологічні основи формування та функціонування системи принципів цивільного судочинства : автореф. дис. ... д-ра юрид. наук : 12.00.03 / В. А. Кройтор; МВС України, Харків. нац. ун-т внутр. справ. - Харків, 2021. - 42 с.
Keywords: Цивільне право. Civil Law. Гражданское право; Україна. Ukraine. Украина; Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; 12.00.03; цивільний процес; цивільне судочинство; принципи права; принципи цивільного судочинства; система принципів цивільного судочинства; основоположні принципи цивільного судочинства; принципи цивільного судочинства, які підкреслюють особливості правосуддя в цивільних справах в Україні; принцип верховенства права; принцип пропорційності; гражданский процесс; гражданское судопроизводство; принципы права; принципы гражданского судопроизводства; civil procedure; civil justice; principles of law; principles of civil justice